Vocational College Students’ Learning Efficiency on The Use of Computer English MOOC in Hybrid Learning - Wei Wei; Noraini Said (Penerbit Universiti Malaysia Sabah, 2023)
With the improvement of educational technology modernization, the promoting effect of network technology on education has been widely concerned by educational circles Massive Open Online Courses (MOOCs) have emerged as a popular platform for learners to access and utilize educational resources. This paper aims to investigate the relationship between various aspects of hybrid learning in the Computer English MOOC platform, including students' learning objectives, methods, concentration, collaborative skills, teacher supervision, and learning efficiency. The research utilizes a quantitative approach to analyze data obtained from 168 vocational college students majoring in computer-related subjects. During the Covid-19 pandemic, it was not always possible for students to go to school in person, but when it came to learning Computer English, they had clear goals. Students were able to get complete and organized information through hybrid learning. And there is a strong relationship between learning cooperation and learning proficiency via hybrid learning. Learning cooperation has the most significant influence on learning proficiency. This study lies in its potential to bridge the knowledge gap regarding the specific factors that impact English language acquisition in the vocational college setting. This research seeks to provide valuable insights and recommendations to inform pedagogical practices, curriculum development, and institutional policies in higher vocational colleges in China.